Crosstalk between phosphorylation and multi-site arginine/lysine methylation in C/EBPs - Leutz, Achim (Landes Bioscience, 2011)
C/EBPs are implied in an amazing number of cellular functions: C/EBPs regulate tissue and cell type specific gene expression, proliferation and differentiation control. C/EBPs assist in energy metabolism, female reproduction, innate immunity, inflammation, senescence and the development of neoplasms. How can C/EBPs fulfill so many functions? Here we discuss that C/EBPs are extensively modified by methylation of arginine and lysine side chains and that regulated methylation profoundly affects the activity of C/EBPs.